Modified sheep blood agar-based medium as an alternative culture media for the cultivation of Mycobacterium Tuberculosis - Tapia, Narciso A.; Adelwisa Ortega, Adviser (2015)
Mycobacterium tuberculosis is cultured in several types of media, which are either expensive or difficult to prepare such as the Lowenstein Jensen medium. In this regard, based on previous studies, plain Sheep?s Blood agar medium was modified (MSBA) by adding 0.25 mg/ml malachite green and was used to isolate Mycobacterium tuberculosis from 65 smear-positive sputum specimens decontaminated with the modified Petroff method. Its efficiency was compared with plain blood agar and Lowenstein Jensen media. And to determine its ability to support growth of Mycobacterium tuberculosis ATCC strain 25177/H37Ra was used as positive control. Selected colonies growing in MSBA and LJ were tested using MGIT TBc Id to confirm the identity of the isolate as Mycobacterium tuberculosis. The results showed that MSBA had a shorter mean days to culture positivity (21.4092) compared to LJ (36.0419), about 2 weeks, and showed the same pattern as the ATCC strain 25177/H37Ra. As to the ability to grow colonies of acid fast bacilli, MSBA had 20% and LJ had 80%. All samples in BA except for one, were contaminated making growth of AFB difficult to establish. Using the McNemar?s test, the difference in the proportion of positive growth between MSBA and LJ was found to be statistically significant (p = 6.83x10-9). Five sputum samples which showed growth in both MSBA and LJ were tested with MGIT TBc Id test and four of them were confirmed to be Mycobacterium tuberculosis, and the fifth was probably non tuberculous mycobacteria (NTM). Contamination was very high with BA (98.5%) compared to MSBA (no contamination) and LJ (1.5%). Based on the results, MSBA may not be as efficient as LJ in primary culture, that is from isolation from specimens. However, it may be very useful as a medium for substitute (for transport to reference lab), since it is easy to prepare, prevents contamination and is able to support the growth of tubercle bacilli
Thesis (MS Public Health, Medical Microbiology)--University of the Philippines Manila
Keywords: Mycobacterium tuberculosis; Blood agar